2015
DOI: 10.1590/s0102-865020150090000001
|View full text |Cite
|
Sign up to set email alerts
|

Repair of surgical wounds in rats using a 10% unripe Musa sapientum peel gel

Abstract: PURPOSE:To investigate the efficacy of a 10% gel of unripe banana (Musa sapientum) peel in treating surgical wounds in rats. METHODS:A longitudinal, prospective, randomized triple-blind study was conducted with 60 Wistar rats (Rattus norvegicus albinus) weighing approximately 400g. The animals were randomly divided into: control group (treated with gel containing no active ingredient) and study group (treated with 10% gel of unripe banana peel). The gel was applied every three days to a 4x4-cm surgical wound c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…With regard to presented results, BPe extract was found to inhibit lipid oxidation better than pulp extract (Someya et al 2002). Recently, it has been shown that gallocatechin extracted from GBPe was effective in the healing of surgical wounds in rats (Von Atzingen et al 2015). Correspondingly, a unique flavonoid named leucocyanidin was found in aqueous extract of unripe plantain pulp, which is now known to be effective in the treatment of gastric diseases (Lewis et al 1999).…”
Section: Health Effects Of Banana Bioactive Compoundsmentioning
confidence: 76%
“…With regard to presented results, BPe extract was found to inhibit lipid oxidation better than pulp extract (Someya et al 2002). Recently, it has been shown that gallocatechin extracted from GBPe was effective in the healing of surgical wounds in rats (Von Atzingen et al 2015). Correspondingly, a unique flavonoid named leucocyanidin was found in aqueous extract of unripe plantain pulp, which is now known to be effective in the treatment of gastric diseases (Lewis et al 1999).…”
Section: Health Effects Of Banana Bioactive Compoundsmentioning
confidence: 76%
“…The residual DNA content was measured by the method described in other studies 35 . Briefly, 50 mg of the dry sample were incubated with DNA extraction buffers of FavorPrep™ Tissue Genomic DNA Extraction mini kit.…”
Section: Methodsmentioning
confidence: 99%
“…The residual DNA content was measured by the method described in other studies. 35 Briefly, 50 mg of the dry sample were incubated with DNA extraction buffers of FavorPrep™ Tissue Genomic DNA Extraction mini kit. The isolation process included tissue lysis, DNA collection, washing, elution, and solvent preparation, orderly.…”
Section: Dna Quantificationmentioning
confidence: 99%
“…Gallocatechin is another phenolic antioxidant identified in banana peel. It has higher amount in the peel (158 mg/100 g of dry weight) than in the pulp (29.6 mg/100 g of dry weight) according to studies on M. cavendishii Lamb [ 68 , 69 ]. Other phenolics found in banana peel include catecholamines, flavanones, flavonols, tocopherols [ 70 ].…”
Section: Body Of Articlementioning
confidence: 99%